Macroeconomic factors influencing interest rates of microfinance institutions in the Latin America and the Caribbean - Karel JANDA; Pavel ZETEK (Agricultural Economics (AGRICECON), 2014)
Agricultural output in developing countries still represents a substantial part of the GDP. This ratio has actually increased in some areas such as the Latin America. As such, there is an increasing importance of microfinance institutions (MFIs) focusing on the activities associated with agriculture and encouraging entrepreneurship in agriculture and in the rural communities in general. The contribution of microfinance institutions consists mainly in providing special-purpose loans, usually without collateral. However, questions exist as to the magnitude and the adequate level of risk of providing micro-credit loans in relation to the interest rates being charged. We review two main approaches to setting interest rates in the MFIs. One approach takes the view that interest rates should be set at a high level due to the excessive risk that these institutions undertake. The second approach is to convince the public of the possibility of reducing these rates through cost savings, increased efficiency, and sharing best practice, etc. Subsequently we econometrically analyse the impact of macroeconomic factors on the microfinance interest rates in Latin America and the Caribbean. We show that these results depend on the chosen indicator of interest rate.